The Nexus of Migration, HIV/AIDS and Food Security in Ethiopia - Kassie, Girma; Asfaw, Woldie; Zeleke, Gete; Drimie, Scott (International Food Policy Research Institute, 2008)
Movement of people, or migration in the positive sense of the term, contributes positively to the achievement of secure livelihoods, and to the expansion of the scope for poor people to figure out pathways out of poverty. Migration does this by ameliorating seasonality and risk, reducing vulnerability, enabling investment in a range of livelihood assets (land improvements, education, livestock etc.), and providing the poor with more of a chance to gain a first purchase on virtuous spirals out of poverty (Ellis, 2003). Migration is part of the socioeconomic dynamics that governs livelihoods both in the source and in the receiving spatial and human ends. Movements of people can be due to so many reasons related to opportunities for improved life or for avoiding the consequences of desperate situations. Employment opportunities, education access, availability of other social services, political safety, social security, land fragmentation and degradation, stigmatization and discrimination particularly in small rural villages, personal risks such as early and forced marriage, family breakdown, and the like can be reasons for people to leave their rural home areas to settle in the cities. Strong social ties, entitlement for assets – such as land – in the rural areas, hopelessness in the city due to lack of social recognition and poor access to social infrastructure, stigmatization and discrimination due to diseases such as HIV/AIDS can, on the other hand, be reasons that drive people back to the rural or to remoter areas.